Contribution of the Pedagogy of Alternation in Soil Conservation Practices - João Carlos Gonçalves; César Augusto Pecoraro; Emanuele Helmann Nunes; Simone Aparecida Quiezi; João Tavares Filho (Brazilian Archives of Biology and Technology, 2024)
Abstract This study aims to show the efficacy of the pedagogy of alternation in soil practices. A compilation of 1200 alternation notebooks of students from 2022 to 2023 was analyzed. The documentary analysis was based on the qualitative meta-synthesis. It was observed that the vast majority of techniques reported in the notebooks matched the reality of the students' properties. The pedagogy of alternation involving soil management and conservation practices has a positive environmental impact on students' rural properties, which supports the practice of sustainable management, contributing to pedagogical instrument development and in the teaching-learning process. Labor is related to social movements and the education of students. Within this framework, it is important to state that this pedagogical system allows students to be free, autonomous, and emancipated in the relationship between agricultural labor and school education.